Answers

2014-11-16T10:51:20+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(2x+1)(3x-1) \\  \\ Use \ FOIL \ Method \ to \ solve \ this \ problem; \\  \\ First;2x \times3x=6 x^{2}  \\ Outer;2x\times-1=-2x \\ Inner;1\times3x=3x \\ Last;1\times-1=-1 \\  \\ 6 x^{2} -2x+3x-1 \\  \\ \boxed{6 x^{2} +x-1} \\  \\ Hope \ this \ Helps:) \\ Domini
0
Thankyouuu!
You can click the "Thank You"button above----You're Welcome:)
2014-11-21T15:23:52+08:00
FOIL method

First: 2x * 3x = 6x²
Outer:  2x * -1 = -2x
Inner: 1 * 3x = 3x
Last: 1 * -1 = -1

Add all but Subtract -2x and 3x since they have the same variable

Therefore;

6x² + x - 1

I hope it helps

0